2021
DOI: 10.1186/s12934-021-01570-x
|View full text |Cite
|
Sign up to set email alerts
|

Study on the mechanism of production of γ-PGA and nattokinase in Bacillus subtilis natto based on RNA-seq analysis

Abstract: Poly-γ-glutamic acid (γ-PGA) and nattokinase (NK) are the main substances produced by Bacillus subtilis natto in solid-state fermentation and have wide application prospects. We found that our strains had higher activity of nattokinase when soybeans were used as substrate to increase the yield of γ-PGA. Commercial production of γ-PGA and nattokinase requires an understanding of the mechanism of co-production. Here, we obtained the maximum γ-PGA yield (358.5 g/kg, w/w) and highest activity of NK during fermenta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“… B. subtilis PGA production was measured using a cetryltrimethylammonium bromide (CTAB) assay as previously described ( 38 , 39 ). Cells were grown in LB broth containing various concentrations of ZnSO 4 or CuSO 4 in LB media overnight at 37°C for 16–18 h. Cells were then pelleted from 15 mL of culture by centrifugation at 10000 × g for 30 min at 4°C and the supernatant was retained.…”
Section: Methodsmentioning
confidence: 99%
“… B. subtilis PGA production was measured using a cetryltrimethylammonium bromide (CTAB) assay as previously described ( 38 , 39 ). Cells were grown in LB broth containing various concentrations of ZnSO 4 or CuSO 4 in LB media overnight at 37°C for 16–18 h. Cells were then pelleted from 15 mL of culture by centrifugation at 10000 × g for 30 min at 4°C and the supernatant was retained.…”
Section: Methodsmentioning
confidence: 99%
“…The isolated supernatants were dotted into the middle of a 0.5% agarose plate containing thrombin and fibrinogen solution at pH 7.4. The diameters (mm) of the clear zones indicated the thrombolytic activity [15]. The positive-control activity was measured with plasmin.…”
Section: Methodsmentioning
confidence: 99%
“…Chungkookjang is comparable to Japanese natto, soybeans fermented with B. subtilis natto for approximately two days. During the fermentation of soybeans, B. subtilis natto produces nattokinase and γ-PGA, which help prevent or treat cardiovascular diseases by improving hypertension and dyslipidemia and reducing blood clotting [15]. B. subtilis, B. licheniformis, and B. amyloliquefaciens also have fibrinolytic activities and produce γ-PGA, but different strains have different efficiencies [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of this by-product on the fermentation of nattokinase is still controversial. Li et al found that the activity of nattokinase was the highest when the production of γ-PGA reached the maximum value; thus Li et al speculated that the γ-PGA produced by Bacillus subtilis during the fermentation process could stimulate the biosynthesis of nattokinase [ 45 ]. Contrarily, Wei et al believed that γ-PGA mixed in nattokinase was an immunogenic substance that would cause allergic reactions in humans that consume it.…”
Section: Study On Fermentation Process Of Nattokinasementioning
confidence: 99%